The law of naval warfare : a comparative analysis in the Islamic law of armed conflict and international humanitarian law - Simsir, Begumhan I. (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2022)
Throughout the previous century, the world focused its armed conflicts mainly on land. As a result, the rules of naval warfare have not been subject to many discussions. However, even if the world did not witness naval battles in the previous years, it does not mean that the states and other entities failed to strengthen and develop their naval forces since the last naval battle. Considering how the majority of the land conflicts are taking place in Muslim territories in this day, it is impossible to ignore the possibility of a naval conflict in Muslim territory. Thus, the importance of understanding and modernizing rules on naval warfare both under Islamic and international humanitarian laws is crucial to make sure that future naval conflicts are just. This article will firstly study the rules on naval warfare in the Islamic law of armed conflict, and analyze its core principles and development. After that, the focus will be placed on the rules on naval warfare under the international humanitarian law. The article will be concluded with an analysis of the relationship between the two laws and how their future should be shaped.